Students Numeracy Literacy Ability in Madrasah Aliyah Through AKM-Class Activities: A Quasi-Experimental Study - Neliana, Neliana; Somantri, Manap; Danim, Sudarwan; Kristiawan, Muhammad; Hamzah, Syukri (UIN Fatmawati Sukarno Bengkulu, 2025)
Numeracy literacy is increasingly central in Indonesia’s school reform agenda, particularly after the implementation of the National Assessment (Asesmen Nasional/AN) and Minimum Competency Assessment (Asesmen Kompetensi Minimum/AKM). This study examines the effect of AKM-class activities on the numeracy literacy ability of Madrasah Aliyah students. A quasi-experimental non-equivalent control group design was employed with 120 Grade XI students (experimental class = 60; control class = 60) from two Madrasah Aliyah schools. The experimental group received AKM-class activities for eight weeks (16 meetings), while the control group underwent conventional instruction. The instrument was an AKM-oriented numeracy test covering four content domains (number, algebra, geometry, and data & uncertainty), three cognitive processes (formulate, employ, interpret), and contextual dimensions (personal, socio-cultural, scientific). Expert review and pilot testing supported instrument quality (Aiken’s V = 0.82–0.94; Cronbach’s alpha = 0.87). Data were analyzed using descriptive statistics, independent and paired t-tests, normalized gain, and ANCOVA. Using simulated but statistically realistic data, pretest scores were equivalent between groups (p = 0.684), while posttest and gain scores significantly favored the experimental group (posttest: p < 0.001; gain: p < 0.001). ANCOVA showed a significant treatment effect after controlling for pretest (F(1,117) = 49.01, p < 0.001, partial η² = 0.295). Domain-level analysis indicated stronger gains in algebra and data & uncertainty, moderate gains in number, and non-significant differences in geometry. These findings suggest that structured AKM-class activities can meaningfully improve numeracy literacy in Madrasah Aliyah, particularly for contextual reasoning and data interpretation skills. The study contributes a practical classroom model for integrating AKM characteristics into regular teaching.